2022
DOI: 10.3390/nu14235069
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Compounds to Improve Post-Exercise Recovery

Abstract: The metabolic and mechanical stresses associated with muscle-fatiguing exercise result in perturbations to bodily tissues that lead to exercise-induced muscle damage (EIMD), a state of fatigue involving oxidative stress and inflammation that is accompanied by muscle weakness, pain and a reduced ability to perform subsequent training sessions or competitions. This review collates evidence from previous research on a wide range of nutritional compounds that have the potential to speed up post-exercise recovery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 229 publications
(378 reference statements)
0
17
0
Order By: Relevance
“…Not only can it improve overall health, but it can also reduce the risk of chronic diseases by decreasing inflammation and oxidative stress. [4,5] Firstly, our study found that patients managed under the ERAS protocol had significantly shorter times to first postoperative bowel movement, first time out of bed, thoracic drainage tube retention, and length of postoperative hospital stay, as well as lower VAS scores on the 2nd and 3rd postoperative days compared to the control group. This is consistent with the findings of D'Andrilli et al, who reported that ERAS-based nursing management could effectively shorten the postoperative hospital stay and alleviate pain for patients undergoing thoracoscopic lobectomy.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Not only can it improve overall health, but it can also reduce the risk of chronic diseases by decreasing inflammation and oxidative stress. [4,5] Firstly, our study found that patients managed under the ERAS protocol had significantly shorter times to first postoperative bowel movement, first time out of bed, thoracic drainage tube retention, and length of postoperative hospital stay, as well as lower VAS scores on the 2nd and 3rd postoperative days compared to the control group. This is consistent with the findings of D'Andrilli et al, who reported that ERAS-based nursing management could effectively shorten the postoperative hospital stay and alleviate pain for patients undergoing thoracoscopic lobectomy.…”
Section: Discussionmentioning
confidence: 81%
“…[ 2 , 3 ] Moreover, regular physical training not only improves overall health and enhances cardiovascular function and insulin sensitivity but also reduces the risk of chronic diseases by decreasing inflammation and oxidative stress. [ 4 , 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Herbal supplements have long been used to treat problems related to stress, inflammation, and sleep, but their effects on post-exercise recovery have not been measured directly. However, the results of studies and investigations at the cellular level have suggested that some of these compounds have the potential to improve post-exercise recovery [62]. In addition to their positive health effects, it is important to note that hop, tea, and mint extracts provide an interesting natural organoleptic profile for elaborated beverages, mainly when they are incorporated with grape juice and lemon juice.…”
Section: Discussionmentioning
confidence: 99%
“…An outside member naive to the nature of this study prepackaged each serving of the assigned supplement in coded bottles, and this person who was not related to the research team was assigned to deliver the supplements to subjects to ensure a double-blind design. The coding information was sealed in an envelope and opened once data collection was complete (7,14,24).…”
Section: Hmb-fa Supplementationmentioning
confidence: 99%